Unlocking the power of adaptive selling: a systematic review and integrative framework - Andreas Angga Saputra; Ahmad Shalahuddin (Lembaga Riset Mutiara Akbar (LARISMA), 2026)
Adaptive selling has become a critical competency for salespeople in increasingly dynamic, competitive, and technology-driven markets. This study aims to synthesize and integrate existing research on adaptive selling by conducting a systematic literature review of peer-reviewed articles published between 2010 and 2021. Using a rigorous screening process and thematic analysis of 85 selected studies, this review identifies five dominant themes in the adaptive selling literature: conceptualization and measurement, antecedents, consequences, moderators and mediators, and contextual factors. The findings reveal that adaptive selling is shaped by a complex interaction of individual factors (such as motivation, self-efficacy, emotional intelligence, and learning orientation), organizational factors (including sales training, leadership style, and organizational culture), and situational contexts (such as product complexity, competitive intensity, and sales settings). Based on these insights, this study proposes an integrative framework that links antecedents, adaptive selling behaviors, mediating mechanisms, and performance outcomes, while also accounting for contextual contingencies and feedback effects. The review highlights the strategic importance of adaptive selling in enhancing sales performance and customer outcomes. Furthermore, it identifies key directions for future research, particularly in relation to digital technologies, virtual selling environments, and the dynamic evolution of adaptive selling over time.